2021
DOI: 10.1111/jfpe.13943
|View full text |Cite
|
Sign up to set email alerts
|

Setting up a diagram process for the elaboration of a new plant‐based beverage from Pinus halepensis seeds: Selection of unit operations and their conditions

Abstract: Aleppo pine seeds are a potential candidate for the production of nondairy milk due to their high protein (26%) and lipid (37%) content and their availability. For the first time, this study presents the implementation of a manufacturing scheme from seeds to final product, including pre-extraction, extraction, and post-extraction (physical and microbiological stabilization), using a 2 fractional factorial screening design. The seven factors were seed soaking time, grinding time, temperature and seed/water rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 34 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…16, In the second search, we identified 141 relevant publications published in 2023. After removing duplicates and carrying out a thorough screening, we identified and included two new studies, 52,53 bringing the total included studies to 33. Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…16, In the second search, we identified 141 relevant publications published in 2023. After removing duplicates and carrying out a thorough screening, we identified and included two new studies, 52,53 bringing the total included studies to 33. Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…All three studies by Tsujita et al, used porcine pancreatic α-amylases in addition to human α-amylases. 42,44,45 Additionally, 17 papers explicitly mentioned or referenced the utilisation of porcine pancreatic α-amylases 16,22,23,[25][26][27][34][35][36][37][38][39]41,43,48,50,52 (Table 2). Four studies indicated or referenced the use of α-amylases derived from a bacterial 24,31,47 or fungal source.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations